THE REPRESENTATIVE ACTIVITIES OF MULTIPLE INTELLIGENCES IN ENGLISH TEXTBOOK ‘WHEN ENGLISH RINGS A BELL’ FOR 8TH GRADERS - Nanik Sri Rahayu (Universitas Islam Lamongan, 2019)
English textbook provided for eight graders is also renewed because of the latest curriculum, 2013 Curriculum. Regarding the theory of Multiple Intelligences, the textbook that the teachers used needs an evaluation in case of helping the teachers to face the students’ diversity in learning style. To evaluate whether English textbook When English Rings a Bell’ for 8th Graders can be regarded as appropriate textbook based on the theory of Multiple Intelligences, this study is held. Thus, this study aims at investigating types of intelligence are included in the activities and what type of intelligences is most dominantly used in the activities provided in ‘When English Rings a Bell’ English Textbook for 8th Graders. Content analysis is used as method in this study and to analyze the data Multiple Intelligence checklist. Among 364 activities analyzed, 105 activities belong to Bodily-Kinesthetic (BKI) which indicated 28,85% as the greatest percentage.Keywords: Multiple intelligence, Teaching and learning activities, Textbook